Analisis Kinerja Non Finansial Internet Banking Ditinjau dari Perspektif Pelanggan - Nurhadi - (Jurnal Aplikasi Manajemen, 2012)
From the marketing perspective, Internet banking is a virtual branch that provides much convenience to customers. This study aims to determine the factors that determine the non-financial performance are reviewed from the perspective of internet banking customers. The population in this study are all customers of Bank Mandiri Branch Mojokerto who use Internet banking service, while the sampling technique using the quota sampling. The analysis technique used was factor analysis. The results of factor analysis that examined 19 variables showed that the internet banking non-financial performance is determined by 6 factors. The first factor consists of account information, balances, account details and a medium for transactions. The second factor that functions as the information rate, error free, and functions to change the pin number, displacement and transfer. The third factor is safety, operations, accuracy, the amount of information that can be given. The fourth factor is the form of presentation in the Internet, many services that can be given. The fifth factor is the information processing time, time access to bank sites, responsiveness. The sixth factor is the introduction and provision of information, customer service.Keywords: Non-financial performace, Internet banking, customer perpective.